PENERAPAN METODE EOQ DALAM PENGELOLAAN PERSEDIAAN BARANG - Yuyun Indri Yanti Wally; Julie Theresya Pelamonia (P3M Politeknik Negeri Ambon, 2025)
This research aims to determine how much inventory is using the Economic Order Quantity (EOQ) method at Sobat Kita Supermarket. This research is a quantitative research with the data used in this research being purchase data, sales data, cost data during 2023. The analysis techniques used are EOQ, safety stock, and reorder points. The results of the research show that inventory management using the EOQ method is more efficient than the methods or policies that have been used by Sobat Kita Supermarket. By using the EOQ method, Sobat Kita Supermarket must order 10 bags of goods in one order with a total purchase frequency of 2 orders in a period of 1 year and requires a safety stock of 3 bags and Sobat Kita Supermarket needs to do a reorder point if the remaining inventory is 3 bags. Keywords: economic order quantity; safety stock; reorder point; total inventory cost